2003
DOI: 10.2337/diabetes.52.2.283
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Rosiglitazone and Metformin on Adipose Tissue Distribution and Glucose Uptake in Type 2 Diabetic Subjects

Abstract: We evaluated the effects of rosiglitazone (4 mg b.i.d.) and metformin (1 g b.i.d.) monotherapy for 26 weeks on adipose tissue insulin-stimulated glucose uptake in patients (n ‫؍‬ 41) with type 2 diabetes. Before and after the treatment, glucose uptake was measured using 2-[18 F]fluoro-2-deoxyglucose and positron emission tomography and adipose tissue masses were quantified using magnetic resonance imaging. Rosiglitazone improved insulin-stimulated whole-body glucose uptake by 44% (P < 0.01 vs. placebo). Mean b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
86
2
6

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 53 publications
15
86
2
6
Order By: Relevance
“…One adipose tissue depot that may behave differently is visceral adipose tissue. A reduction in postprandial NEFA generation from this depot in response to rosiglitazone could account for the observed lowering of postprandial NEFA concentrations and would be consistent with the reduction of visceral adipose tissue mass with rosiglitazone found by other authors [52,53].…”
Section: Discussionsupporting
confidence: 89%
“…One adipose tissue depot that may behave differently is visceral adipose tissue. A reduction in postprandial NEFA generation from this depot in response to rosiglitazone could account for the observed lowering of postprandial NEFA concentrations and would be consistent with the reduction of visceral adipose tissue mass with rosiglitazone found by other authors [52,53].…”
Section: Discussionsupporting
confidence: 89%
“…This is the capacity for muscle to shift reliance between glucose and lipids in response to insulin, which is impaired in individuals with large subcutaneous fat cells [32]. In quantitative terms, more glucose is taken up by subcu-taneous adipose tissue than by visceral adipose tissue following insulin infusion and this regional difference is enhanced following treatment with insulin sensitisers (biguanides or glitazones) [33,34]. With regard to plasma lipids, visceral adipose tissue is drained by the portal vein directly into the liver where the production of circulating lipids and lipoprotein takes place.…”
Section: Discussionmentioning
confidence: 99%
“…Given that AMPK activation (5-aminoimidazole-4-carboxamide ribonucleoside) with AICAR has been recently shown to inhibit glucose uptake and lipogenesis in adipocytes (49), our results are consistent with increased adipose tissue glucose uptake and lipid storage. In support of this contention, Virtanen et al (50) demonstrated that enhanced glucose uptake into adipose tissue makes a significant contribution to rosiglitazoneinduced insulin sensitization in patients with newly diagnosed type 2 diabetes. Our observations of increased adipose tissue mass combined with elevated adipose GLUT4 content and reduced AMPK activation provide a potential mechanism for increased adipose tissue glucose uptake after rosiglitazone treatment.…”
Section: Fig 3 Skeletal Muscle Ampk Activity and Protein Expressionmentioning
confidence: 92%